1983
DOI: 10.1177/019263658306745910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Year-Round Junior High School Operation

Abstract: The potential for improvement in ed ucational quality by converting to a year-round school operation must in volve far more than the simple con version of the school calendar, say these writers, who report the re sults of a study of one district that did convert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The major reasons listed by the administrators were the difficulty in scheduling students and the lack of adequate clerical and computer support (Young and Berger, 1983).…”
Section: Round Educationmentioning
confidence: 99%
“…The major reasons listed by the administrators were the difficulty in scheduling students and the lack of adequate clerical and computer support (Young and Berger, 1983).…”
Section: Round Educationmentioning
confidence: 99%
“…Also, Skirbekk (2006) assessed how the duration of primary and secondary schooling affects student performance in the final year of secondary school in Switzerland and concluded that there was no significant impact of the school duration on student performance in mathematics and science tests scores. Young and Berger (1983), Pittman, Cox, and Burchfiel (2010) who also studied the changes in achievement that can be expected from extending the school year found out that extending the school year will not result in improved or better academic performance.…”
Section: Items 3 Years 4 Yearsmentioning
confidence: 99%
“…Formative Experiences in Kansas, Colorado, andOklahoma, 1947 to 1955 After service in World War II, during which his Army unit liberated a Nazi death camp, Young used his GI Bill education benefits to complete his formal education. He earned his associate's degree at Iola Junior College (now Allen County Community College) and his bachelor's (1948) and master's (1949) degrees at Kansas State Teachers College-Pittsburg (KSTC-P), where his thesis examined practices in secondary school libraries in eight Kansas school districts (Young, 1949), a subject of interest 35 years later (Young & Berger, 1983).…”
mentioning
confidence: 99%